Prevalence, severity and explanatory factors of tooth wear in Arab populations. (January 2019) - Awad, M.A.; El Kassas, D.; Al Harthi, L.; Abraham, S.B.; Al-Khalifa, K.S.; Khalaf, M.E.; Al Habashneh, R.; Bartlett, D.
Abstract: Objectives: The aim of this study was to assess the prevalence and severity of tooth wear and related risk indicators in six Arab countries. Methods: This multicenter, multinational cross-sectional study was conducted among 2924 participants between the ages of 18–35 years old from six Arab countries. Calibrated dentists assessed tooth wear using the Basic Erosive Wear Examination Index (BEWE). Participants were also asked to complete a questionnaire that assessed their dietary and oral health habits. Each participant was identified by the sextant with the highest BEWE score in the upper and lower jaws. Results: Odds ratios were estimated for correlates of tooth wear anterior and posterior regions. Oman had the highest prevalence of BEWE score 3 (N = 255 (60.2%)). Overall, the highest BEWE score 3 was observed on the incisal edge of the upper anterior teeth (N = 602 (20.6%)) and in the lower left posterior region (sextant 6) on the occlusal surface (N = 466 (15.9%)). Correlates of severe tooth wear in both regions were eating or drinking more than six times per day, age and education. Drinking soft drinks "once a day" was significantly associated with severe tooth wear in the posterior region (OR: 1.3, 95% CI:1.05, 1.6). Brushing teeth more than twice a day was inversely associated with tooth wear in the anterior region (OR:0.75, 95% CI: 0.57, 0.97). Conclusion: The prevalence of tooth wear in Arab populations is relatively high, specific preventive and therapeutic measures should be developed to target people at higher risk of this condition. Clinical Significance: Tooth wear is now regarded as a significant oral health problems, dentists should advise their patients about dietary and oral health habits that can lead to severe tooth wear.